1988
DOI: 10.1021/bi00406a049
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic properties of proteolytic derivatives of human .alpha.-thrombin

Abstract: The use of derivatives of alpha-thrombin obtained by limited proteolysis, that have only a single peptide bond cleaved, allowed the unequivocal correlation between the change in covalent structure and alteration of the enzymatic properties. beta T-Thrombin contains a single cleavage in the surface loop corresponding to residues 65-83 of alpha-chymotrypsin [Birktoft, J. J., & Blow, D. M. (1972) J. Mol. Biol. 68, 187-240]. Compared with alpha-thrombin, this modification had a minor effect on the following: (1) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
98
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 26 publications
9
98
0
1
Order By: Relevance
“…S1). A key cleavage site used to generate ligand-impaired ␥-thrombin occurs at the Arg 75 -Tyr 76 site (31). With the resolubilized thrombin samples, the ABE I segment containing residues 65-84 was still intact and could be isolated from thrombin following a peptic digest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1). A key cleavage site used to generate ligand-impaired ␥-thrombin occurs at the Arg 75 -Tyr 76 site (31). With the resolubilized thrombin samples, the ABE I segment containing residues 65-84 was still intact and could be isolated from thrombin following a peptic digest.…”
Section: Methodsmentioning
confidence: 99%
“…A strategy to alleviate this concern would be to work with a thrombin species where the ABE I site is no longer available for ligand binding. This condition may be achieved by using ␥-thrombin, a proteolytically derived variant of this serine protease that contains a disrupted ABE I region (31). With this variant, the ABE II region would be intact.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that prothrombin and thrombin have two separate electropositive exosites (anion binding exosite I, ABE-I, and anion binding exosite II, ABE-II) that are responsible for the majority of the functions of the molecules (30 -39). Whereas ABE-I has been involved in the binding to thrombomodulin (40), fibrinogen (41), PAR1 (42), the COOH-terminal hirudin peptides (43), and heparin cofactor II (44) among others, ABE-II was found to be involved in the interaction with protease nexin (45) and antithrombin III (44). Data from separate laboratories have demonstrated that both exosites bind factors V and VIII (33,34,35).…”
mentioning
confidence: 99%
“…The number of thrombin structures currently deposited in the Protein Data Bank exceeds 150, but not a single one of them was obtained in the absence of Na ϩ , inhibitors, or effector molecules. The presence of inhibitors, either at the active site or exosite I, is made necessary by the tendency of thrombin to cleave itself at Arg-77a in exosite I (13). The cleavage initiates a cascade of autoproteolytic steps that culminates in the excision of the Arg-67-Arg-77a fragment of exosite I and the conversion of the native ␣-thrombin into ␥-thrombin.…”
mentioning
confidence: 99%